Distention Media in Hysteroscopy for Diagnostic and Operative Procedure - Hadisaputra, Wachyu (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: Hysteroscopy is the "gold-standard" procedure used to describe the morphology of uterine cavity and the presence of intrauterine lesions and it is a minimally invasive intervention that can be used to diagnose and treat many intrauterine and endocervical problems. Hysteroscopy requires uterine distention for the effective visualization of the uterine cavity and the clearing of blood and tissue debris. Options for uterine distention include insufflation with carbon dioxide (CO2) gas, and instillation with electrolytic and nonelectrolytic liquid distention media. In this review, we would like to review known available distending media and its characteristics for diagnostic and operative hysteroscopy. Method: Literature review. Conclusion: Carbon dioxide and normal saline are the most preferable distention media for diagnostic hysteroscopy. There is no significant difference between these medium in terms of visualization quality, but most practitioners prefer to use normal saline because of itâs availability and acceptability, quick performance, fewer additional procedures, more satisfaction rate, and good visualization. Low viscosity fluids are the most preferable media for operative hysteroscopy. Low viscous-electrolytic fluids, mostly normal saline is recommended in operative cases using mechanical, laser or bipolar energy that requires no electricity. Nonelectrolytic low-viscosity fluids are most preferable for extensive operative procedures using electrosurgery. Mannitol are chosen over glycine or sorbitol when using monopolar electrosurgery. [Indones J Obstet Gynecol 2010; 34-3: 150-4] Keywords: hysteroscopy, distention media, diagnostic procedure, operative procedure